The Role of Emotional Storytelling in Product Promotional Videos on Purchase Intention: A Systematic Literature Review with Emphasis on Skincare Service Products - Sujatmiko, S.; Mattarima, M.; Panus, P.; Samalam, Abdul Gafar; Lawalata , Izaac L.D (Manunggal Halim Jaya, 2026)
This study aims to systematically examine the role of emotional storytelling in product promotional videos and its influence on consumers' purchase intention, with a particular emphasis on skincare service products. Emotional storytelling has emerged as a persuasive marketing strategy that leverages affective narratives to foster consumer-brand relationships, build trust, and enhance behavioral responses. Given the increasing prevalence of emotionally driven promotional content across digital platforms, especially within the visually rich skincare industry, this research conducts a structured literature review to synthesize theoretical perspectives and empirical findings. Utilizing a descriptive quantitative approach, this study reviewed 30 peer-reviewed articles published between 2000 and 2024, focusing on emotional narrative structures, psychological mechanisms, and behavioral outcomes. The findings indicate that emotional storytelling positively impacts consumer purchase intention by fostering narrative transportation, emotional contagion, and perceived authenticity. Specifically, narrative coherence, emotional valence, and brand relatability were identified as key drivers of consumer engagement. In the skincare sector, emotionally charged videos that depict transformation, self-care, and identity alignment proved to be especially effective in motivating purchasing behavior. Moreover, platform-specific dynamics such as video format and interactivity were found to moderate storytelling effectiveness. The study contributes to the theoretical development of affective marketing and offers practical guidance for brands aiming to craft emotionally resonant promotional content. It also proposes a conceptual framework for future empirical testing on emotional storytelling and consumer behavior in the context of beauty and self-care services.